“So Contrary and Provoking”: Love in Louisa May Alcott’s An Old-Fashioned Girl (1869) - Sirpa Salenius (European Journal of American Studies, 2022)
Although Louisa May Alcott’s An Old-Fashioned Girl (1869) promotes conventional gender expectations and traditional values, at the same time it depicts heterosexual marriage as mercenary and dispassionate. It proposes women’s choice to become self-sustaining as a positive alternative to marriage. Thus, the narrative seems to destabilize the same conventionality it promotes: “spinsterhood,” independent career women, and same-gender affection all appear in a positive light. Beyond Alcott’s conventional plot, the book proposes some progressive, provocative, and ambiguous scenarios the unveiling of which requires the readers’ collaboration.